HUBUNGAN KEJADIAN ISPA PADA BALITA DENGAN PEMUKIMAN DI SEKITAR TRANSPORTASI TONGKANG BATUBARA DI SUNGAI BARITO KECAMATAN TABUNGANEN TAHUN 2011 - Hasanah, Robiah; Zubaidah, Tien; Noor, Frieda Ani (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2014)
Acute Respiratory Infection (ARI) is a respiratory infection that can last up to 14 days. Barito River is one of the rivers that flow into the coal barge transportation. Based on field data, any impact caused by the transportation of coal barges is a decrease in air quality due to increase in coal dust blown into the densely populated settlement that could lead to respiratory diseases. This study aims to analyze the relationship between the incidence of respiratory infection in infants with settlements that are near (≤ 500 m) and deep (> 500 m) from the coal barge transportation flow. This study was an observational analytic study design correlation. The results of this study indicate that Ho is accepted which means there is no relationship between the incidence of respiratory infection in infants with settlements close range (≤ 500 m) with a flow of barge transportation of coal in the Barito River. And there was no correlation between the incidence of respiratory infection in infants with residential distance away (> 500 m) from the coal barge transportation flow in the Barito River. Based on these results it is necessary to further study the most relevant factors that cause respiratory events in children under five in sub Tabunganen enough. Keywords: ARI, the flow of transportation, distance settlement